"It just reeks of Italianism" Traces of Italian Opera in A Life for the Tsar. - Helmers, Rutger (Oxford University Press, Oxford, 2010)
RESUMEN: Although it is almost a truism nowadays to say that the style of Mikhail Glinka's operas is Italianate, little effort has yet been made to investigate this aspect of his work in any detail. A comparison of Glinka's A Life for the Tsar (1836) with contemporary Italian operas not only offers insights into his compositional methods, but also provides a more nuanced view of the construction of Russian national music by showing the complexity of Glinka's relation with contemporary bel canto opera.